2021
DOI: 10.1002/jmrs.559
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medical radiation science graduates’ early career principal place of practice: a retrospective cohort study

Abstract: Introduction While studies have investigated influences on graduate practice locations of other health professionals, especially medicine, none have investigated practice locations of medical radiation science (MRS) graduates. This study aimed to explore factors influencing the registered principal place of practice (PPP) of diagnostic radiography, radiation therapy and nuclear medicine graduates from the University of Newcastle (UON), Australia, in their second post‐graduate year. Methods Data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some disciplines may have unique factors that influence rural practice. For medical radiation science students, specialty affected rural practice, as did number and duration of rural placements and rural background 15 . Diagnostic radiography graduates were significantly more likely to be practising rurally than those in nuclear medicine.…”
Section: Rural Placements and Rural Practice Intentionmentioning
confidence: 99%
“…Some disciplines may have unique factors that influence rural practice. For medical radiation science students, specialty affected rural practice, as did number and duration of rural placements and rural background 15 . Diagnostic radiography graduates were significantly more likely to be practising rurally than those in nuclear medicine.…”
Section: Rural Placements and Rural Practice Intentionmentioning
confidence: 99%
“…Moreover, the present study also found that a number of allied health students originated from rural areas later practised in rural and remote areas. Several previous studies have found that health professionals who were from rural origin were more likely to practice in rural areas 12–16 . However, given our limited data, a comprehensive study is required to examine the contribution of UDRH's rural placement program on addressing rural workforce maldistribution in SA.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies have found that health professionals who were from rural origin were more likely to practice in rural areas. [12][13][14][15][16] However, given our limited data, a comprehensive study is required to examine the contribution of UDRH's rural placement program on addressing rural workforce maldistribution in SA.…”
Section: T a B L E 1 Proportion Of The 2019mentioning
confidence: 99%
“…A recent Australian study assessing factors related to non‐metropolitan primary place of practice (PPP) for Medical Radiation Science graduates found that location of origin, and type of Medical Radiation Science discipline were significant predictors of rural PPP after controlling for other variables. Graduates of rural origin were more likely to have a rural PPP (OR = 3.54) than those from metropolitan locations, with diagnostic radiography graduates more likely to have a rural PPP (OR = 5.46) than nuclear medicine graduates 14 …”
Section: Introductionmentioning
confidence: 99%
“…Graduates of rural origin were more likely to have a rural PPP (OR = 3.54) than those from metropolitan locations, with diagnostic radiography graduates more likely to have a rural PPP (OR = 5.46) than nuclear medicine graduates. 14 …”
Section: Introductionmentioning
confidence: 99%